Integration Of Mobile Teacher Education And Islamic Religious Education In Facing The Society 5.0 Era - Miftakhul Ulumiyah (Journal of Social Science and Economics, 2022)
The rapid development of the era in the field of technology has had a tremendous impact on people's lives. This impact was also felt in the education sector. The Indonesian era initiated in Germany has now been broken with the era of society initiated by the Japanese state. Society 5.0 is a concept developed for the sake of forming a super smart society that has a behavior pattern that optimizes the use of the Internet of things, Big Data, and Artificial Intelligence as solutions for a better society. In dealing with this, the world of education in Indonesia has issued several policies, one of which is the teacher mobilization program as a result of the 5th episode of the independent learning policy. Apart from that, strengthening the morale of students has also been intensified through Islamic religious education which is included in the national curriculum. With these policies, it is hoped that good integration will be created to prepare Indonesian education for the 0.5 era.